Analysis of Nutritional Status of Batita in Taman Rahayu Village, Working Area of Puskesmas Setu II Bekasi - Mamah; Nanik Yuliwati (PT FORMOSA CENDEKIA GLOBAL, 2023)
According to the results of the Indonesian Nutrition Status Study (SSGI) in children aged 0-59 months out of 153,228 it was found that 7.1% of children were wasted with the highest cases being in Maluku (12.0%) and the lowest being in Bali (3). ,0 %). Meanwhile, in West Java, 5.3% of children were found. The aim of this study was to analyze the nutritional status of toddlers in Taman Rahayu Village, the working area of ​​the Setu II Health Center in Bekasi. This research is an analytic survey research using a cross sectional research design with a population of 357 people and a sample of 79 people selected using random sampling technique. Data was taken using a questionnaire which was then processed using a statistical program. The research found that most of the toddlers (75.9%) were well nourished and only 6.3% of toddlers were malnourished. Most of them received poor parenting (72.2%), had low income (77.2%), had no history of infectious diseases (94.9%) and had poor knowledge (67.1%). The results of the statistical analysis found factors related to the nutritional status of toddlers, namely upbringing (p value = 0.008), while unrelated factors were income (p value = 0.107), history of infectious diseases (p value = 0.224), and knowledge (p value = 0.089).